Concentração de citocinas e atividade funcional de células mononucleares do colostro humano em função do parto e paridade - Deluque, Alessandra Lima (2017)
Breast milk presents changes in its composition that may be related to maternal nutrition, changes throughout the day and during the same feeding, and maternal characteristics. To evaluate the concentration of cytokines in the supernatant and functional activity of human colostrum mononuclear cells as a function of parity and parity. Sixty samples of colostrum were collected, 15 of each group, with a volume of approximately 8 mL. The groups were separated into four groups: Normal Primigestas, Normal Multigesta, Cesariana Primigestas and Cesariana Multigestas. Quantification of the superoxide dismutase enzyme activity in colostrum supernatant was used to determine the control group. Doses of the cytokines present in the human colostrum supernatant were performed using the flow cytometry methodology to determine immunomodulators. The assays followed with the cell portion of the human colostrum: superoxide anion (O2-) dosage, phagocytosis index and microbicidal activity. After statistical analysis, the relevant cytokines to the group of nursing mothers were IL-6 and IL-8, which became immunomodulators for the assays that used the cell portion. The group Normal Multigesta presented as the control group, through the quantification of the enzymatic activity of Cu-Zn-SOD. For IL-6-modulated cell activation, the O2- dosage demonstrated significant differences with increase when cells were incubated with IL-6 and with EPEC in comparison to spontaneous release. This modulation is evident for the Normal Primigesta group in incubation with IL-6 in the absence and presence of EPEC, obtaining a significant increase. In analyzing the maternal characteristics separately, the puerperal women of normal birth and primigravidae parity confirmed the high levels of O2- release when the characteristics are studied together. Phagocytosis index and microbicidal activity increased for all groups. In the IL-8 modulation, there was a decrease in the O2- release in all groups studied for cells incubated with IL-8 and with EPEC together with IL-8, the index of phagocytosis and microbicide increased in all groups. Groups with exception for the Cesarian group Primigesta in the phagocytic activity. When the maternal characteristics are considered separated, the puerperium of cesarean delivery and multigestive parity presented elevated levels of O2- release. Immunological aspects in collaboration with the type of parity and parity of mothers contribute to the scientific basis for ensuring a postpartum period and adequate breastfeeding, thus enhancing infant nutrition by seeking the growth and development of the child's immune system and Preventing future diseases.